2019
DOI: 10.1212/wnl.0000000000006834
|View full text |Cite
|
Sign up to set email alerts
|

Normal cerebral cortical thickness in first-degree relatives of temporal lobe epilepsy patients

Abstract: ObjectiveTo examine cerebral cortex thickness in asymptomatic first-degree relatives of patients with mesial temporal lobe epilepsy (MTLE).MethodsWe investigated 127 asymptomatic first-degree relatives of patients with MTLE due to hippocampal sclerosis (HS) (mean age ± SD = 39.4 ± 13 years) and 203 healthy control individuals (mean age ± SD = 36.0 ± 11 years). Participants underwent a comprehensive clinical evaluation and structural brain MRI at 3 study sites. Images were processed simultaneously at each site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
1
10
1
Order By: Relevance
“…Alhusaini and colleagues summarized the literature on familial traits in epilepsy before 2016 and found a probable familial component to hippocampal structural alterations, particularly in patients with TLE with a strong family history for seizures . Previous cohorts of sporadic TLE, including two recent studies, did not find significant hippocampal changes in unaffected relatives of patients with sporadic TLE, whereas one study observed a trend for bilaterally smaller hippocampi in unaffected siblings, similar to our results. One possible reason for the failure to detect hippocampal atrophy in the relatives of sporadic patients in previous studies is the use of an automated segmentation pipeline implemented in Freesurfer, which is known to be unreliable in small, sclerotic, or malrotated hippocampi .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Alhusaini and colleagues summarized the literature on familial traits in epilepsy before 2016 and found a probable familial component to hippocampal structural alterations, particularly in patients with TLE with a strong family history for seizures . Previous cohorts of sporadic TLE, including two recent studies, did not find significant hippocampal changes in unaffected relatives of patients with sporadic TLE, whereas one study observed a trend for bilaterally smaller hippocampi in unaffected siblings, similar to our results. One possible reason for the failure to detect hippocampal atrophy in the relatives of sporadic patients in previous studies is the use of an automated segmentation pipeline implemented in Freesurfer, which is known to be unreliable in small, sclerotic, or malrotated hippocampi .…”
Section: Discussionsupporting
confidence: 87%
“…In support of this, cortical thinning was previously associated with seizure frequency and duration of epilepsy and we also found a correlation with duration of epilepsy (Appendix ). On the other hand, two previous studies found altered cortical morphology driven by surface area contractions in siblings of patients with TLE, but there were no changes in cortical thickness . In our study, significant surface area abnormalities were found in patients with TLE but not in their siblings (Appendix ).…”
Section: Discussioncontrasting
confidence: 74%
“…Similarly, previous work in temporal lobe epilepsy failed to identify MRI-derived cortical thickness changes as a structural endophenotype, while other morphologic features, including localized contractions of cerebral surface area, showed correlated topologic alterations between patients and their firstdegree relatives. 14,46 In healthy people, cortical thickness is believed to be largely determined by prenatal and postnatal developmental processes. 47 Progressive cortical atrophy associated with longer disease duration and increased seizure frequency, a phenomenon often reported in epilepsy, likely represents a marker of disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…12 In epilepsy, most effort has been dedicated to exploring MRI endophenotypes in focal syndromes, primarily temporal lobe epilepsy. 13,14 Conversely, structural MRI studies of JME have so far described group-level changes between patients and healthy controls, which have been interpreted as disease effect. 2 Our purpose was to assess the endophenotypic potential of structural MRI in JME.…”
mentioning
confidence: 99%
“…Interestingly, both Alhusaini et al and Yaakub et al found reduced cortical surface areas in anteromedial temporal regions of asymptomatic siblings of sporadic MTLE‐HS patients, but no significant changes in cortical thickness. This lack of cortical thickness changes has been confirmed in 127 asymptomatic first‐degree relatives of MTLE‐HS patients from three independent cohorts, each with a healthy control group . These findings altogether indicate that the previously characterized progressive cortical thinning in patients with MTLE‐HS is not heritable and is likely driven by disease‐related factors, whereas changes in the cortical surface area may represent an inherited trait that preceded seizure onset.…”
mentioning
confidence: 54%